A relação entre Física e Arte na Literatura Científica: uma investigação sobre como as pesquisas da área de ensino de física na literatura científica brasileira têm abordado essa relação - Rocha, Eduardo Antonio Fernandes (Universidade Federal de São Carlos, 2025)
This study investigates how the relationship between physics and art has been addressed in the Brazilian scientific literature in the field of physics education. It is a qualitative bibliographic analysis based on articles published between 2010 and 2024 in three Brazilian physics education journals classified as A by Qualis in the 2017–2020 quadrennium. In total, 22 articles were identified as the corpus of analysis. Inspired by Bardin’s Content Analysis methodology, the study developed two categorization criteria to examine the articles: the articulation criterion, which describes how physics is related to art through five analytical categories (cultural, motivational, interdisciplinary, integrative, and contextualizing); and the function criterion, which defines the role attributed to the relationship between physics and art in the articles, with four analytical categories (critical, formative, instrumental, and epistemological). The results reveal that the formative function was the most prevalent, highlighting the potential of the relationship between physics and art to broaden worldviews and foster a more sensitive and meaningful scientific education. Although the instrumental function remains common, its isolated use tends to limit the pedagogical potential of the relationship. Cultural and integrative articulations also stand out as the most versatile and formative.
The relatioship between Physics and Art in Scientific Literature: an investigation into how physics education research in brazilian scientific literature has addressed this relationship
Keywords: Física e Arte; Ensino de Física; Análise de Conteúdo; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade